2013
DOI: 10.1007/s11142-013-9223-1
|View full text |Cite
|
Sign up to set email alerts
|

A theory of voluntary disclosure and cost of capital

Abstract: This paper explores the links between firms' voluntary disclosures and their cost of capital. I relate the differences in costs of capital between disclosing and nondisclosing firms to disclosure frictions and equity risk premia. Specifically, I show that firms that voluntary disclose their information have a lower cost of capital than firms that do not disclose. I also examine the extent to which reductions in cost of capital map into improved risk-sharing and/or greater productive efficiency. I prove that hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(77 citation statements)
references
References 61 publications
0
71
0
3
Order By: Relevance
“…Accordingly, increasing disclosure up to the good-practice level has an appreciable effect on the COEC, but the effect of further disclosure beyond this level is marginal (Armitage and Marston, 2008). Similarly, Cheynel (2013) finds that firms making voluntary disclosures have a lower COEC than firms that do not disclose. Yet, if there is more voluntary disclosures among the sample firms (i.e., lower disclosure frictions), it is found that the association between voluntary disclosure and COEC turned to be positive for both disclosing and non-disclosing firms.…”
Section: Voluntary Disclosure and The Coecmentioning
confidence: 96%
“…Accordingly, increasing disclosure up to the good-practice level has an appreciable effect on the COEC, but the effect of further disclosure beyond this level is marginal (Armitage and Marston, 2008). Similarly, Cheynel (2013) finds that firms making voluntary disclosures have a lower COEC than firms that do not disclose. Yet, if there is more voluntary disclosures among the sample firms (i.e., lower disclosure frictions), it is found that the association between voluntary disclosure and COEC turned to be positive for both disclosing and non-disclosing firms.…”
Section: Voluntary Disclosure and The Coecmentioning
confidence: 96%
“…8 Such factor structures are commonly used to clarify in the model the sources of common risks (see, among other examples, Hughes et al, 2007, Caskey et al, 2015, and Cheynel, 2013. As shown by Caskey et al (2015), similar results can also be obtained with a (more general) approach in which the covariance matrix can be written in terms of an 'approximate' factor structure.…”
Section: Comparative Statics On Information and The Cost Of Capitalmentioning
confidence: 88%
“…22 We refer to Christensen and Qin (2013) for a formal treatment of disagreement in a dynamic trading model. 23 See Jorgensen and Kirschenheiter (2003), Jorgensen andCheynel (2013). See also Clinch and Verrecchia (2013) for a recent study of this question within a model in which the private information is not fully diversifiable.…”
Section: Voluntary Disclosurementioning
confidence: 99%
See 1 more Smart Citation
“…The findings of Easley and O'Hara (2004) suggest that more disclosures by a firm might lower its cost of capital, due to a reduced information risk. Cheynel (2013) employs a model where a firm's disclosures are voluntary, and shows that firms that disclose their information feature lower capital costs than firms that do not disclose.…”
Section: Literaturementioning
confidence: 99%